2016
DOI: 10.1111/lang.12171
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Effect of Bilingual Immersion Schooling on Cognitive Control and Intelligence*

Abstract: Throughout the past century, the effects of bilingualism on general cognition have been extensively explored. Studies evolved from a negative to a more positive perspective, but longitudinal assessments of effects of bilingualism are scarce. This study investigated the long‐term effect of becoming a bilingual on the development of general intelligence and cognitive control. We followed 27 five‐year‐old children initiating bilingual kindergarten and 27 age‐matched controls enrolled in monolingual kindergarten. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 44 publications
8
36
1
1
Order By: Relevance
“…Relatedly, the group differences in SES are likely the consequence of a self-selection bias in the sense that, in Belgium, although a priori open to anyone, immersion education is known to be particularly attractive to a socially more privileged public. Whereas Woumans et al (2016) observed a clear advantage in nonverbal intelligence for immersed children, we found a similar advantage, which in our study however disappeared after controlling for differences in SES. This points towards a need for longitudinal studies on immersion education, which are less sensitive to baseline differences in potentially confounding background variables.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Relatedly, the group differences in SES are likely the consequence of a self-selection bias in the sense that, in Belgium, although a priori open to anyone, immersion education is known to be particularly attractive to a socially more privileged public. Whereas Woumans et al (2016) observed a clear advantage in nonverbal intelligence for immersed children, we found a similar advantage, which in our study however disappeared after controlling for differences in SES. This points towards a need for longitudinal studies on immersion education, which are less sensitive to baseline differences in potentially confounding background variables.…”
Section: Discussioncontrasting
confidence: 88%
“…Bialystok and Barac (2012), however, observed a positive relationship between the duration of immersion education and executive control. Woumans et al (2016) showed that after one year of immersion education, there was no advantage on a Simon task for 5-year-old immersed children, although there was an advantage for the immersed group on nonverbal intelligence. Nicolay and Poncelet (2013, 2015) compared executive control abilities of 8-year-old children immersed for three years with those of monolinguals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Xie and Pisano (2019), intelligence was reported a significant predictor of congruent trials in the flanker task. In Woumans et al (2016), a longitudinal study was carried out to examine whether immersion bilingual schooling could improve cognitive control. Their results found that the children attending bilingual kindergarten improved not only in cognitive control but also in intelligence.…”
Section: Discussionmentioning
confidence: 99%